Hubungan Kepercayaan Diri Dengan Komunikasi Interpersonal Siswa - Ignasius Kurnia; Matilda Pia Bone; Yohanes Demon (Pusat Riset dan Inovasi Nasional, 2024)
The focus of this research is to see whether there is a relationship between self-confidence and students' interpersonal communication. The aim of this research is to determine the significant relationship between self-confidence and interpersonal communication of class VIIIC students at Sancta Familia Kupang Catholic Middle School in the 2023/2024 academic year. This type of research is quantitative descriptive research. The variables in this research are the independent variable (X) self-confidence and the dependent variable (Y) interpersonal communication. The population is all students in class VIIIC of Sancta Familia Kupang Catholic Middle School for the 2023/2024 academic year. The sample in this research consisted of 23 students. The data collection tool used was a self-confidence questionnaire with interpersonal communication. The data analysis technique used is product moment correlation. The results of research data analysis show a Pearson Correlation value of 0.635 with a significance value obtained of 0.00 <0.05, including the strong category. The results of this research data analysis show that there is a significant relationship between self-confidence and interpersonal communication of class VIIIC students at Sancta Familia Kupang Catholic Middle School in the 2023/2024 academic year.